Analysis of the effect of interpersonal communication, teamwork, and work discipline on the performance of outsole employees - Martha Ayerza Esra; Armi Bakar; Nurlela Nurlela; Toni Sinambela; Amelia Sandra (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This learning aims to analyze the influence of interpersonal communication, Teamwork, and work discipline on the Performance of outsole employees at PT. Multi Self-Creation. This study used a quantitative approach with a population of 50 employees. The method of data collection uses the form of interviews and questionnaires. The data analysis technique used is data analysis used is multiple linear regression analysis and hypothesis testing. The results showed that partial interpersonal communication has a significant effect on employee performance, Teamwork has a substantial impact on employee performance, and work discipline has a significant effect on employee performance. Simultaneously interpersonal communication, Teamwork, and work discipline have a considerable impact on employee performance. It is recommended to improve the Performance of employees in the future, should the leadership of PT. Multi Kreasi Mandiri can: 1) Provide examples to employees to open active and relevant discussions so that Interpersonal Communication can run effectively, 2) Create Teamwork which is better to create a sense of belonging to the company, 3. Improve employee work discipline by controlling the implementation of SOPs continuously.